Penggunaan Konteks dalam Implementasi Pendidikan Matematika Realistik Indonesia oleh Mahasiswa - Anisa Fatwa Sari; Kurnia Noviartati (Jurnal Pendidikan Matematika : Judika Education, 2022)
This study aims to describe how student mathematics teacher candidates use context in learning mathematics. A qualitative approach is used as a research method with supporting instruments, namely questionnaires and interview guidelines. The subjects of this research are mathematics education students who program PMRI courses. Data collection techniques are documentation of student reports, giving questionnaires and interviews about the context of mathematics. Data were analyzed by coding to develop descriptions and themes to answer research questions. The results showed that students understood the context as limited to problems related to everyday life. Students have not been able to implement PMRI because there are students who focus on solving mathematical problems by students. In conclusion, students have not utilized the potential of the context so that students can learn to reconstruct mathematical concepts and hone mathematical thinking processes through problem solving. Keywords: Mathematical Context, PMRI, Mathematization, RME